Efficient design of an artificially roughened solar air heater with semi-cylindrical side walls: CFD and exergy analysis. (1st September 2020) - Nidhul, Kottayat; Yadav, Ajay Kumar; Anish, S.; Arunachala, U.C.
Highlights: CFD and exergy analysis of a solar air heater with semi-cylindrical sidewalls is proposed. Semi-cylindrical sidewalls enhance the strength of secondary flow in a ribbed SAH. A significant enhancement in the effectiveness parameter of 2.27 is obtained. Lower exergy destruction leads to an enhancement of 95% in exergetic efficiency. The proposed design outperforms ribbed rectangular SAHs for a wide range of Reynolds number. Abstract: Solar air heater (SAH) with semi-cylindrical sidewalls and W-baffles is analyzed for energy and exergy efficiency in the turbulent flow regime. Computational fluid dynamics (CFD) analysis is carried out for a fixed baffle inclination ( β ) and varying the relative baffle height ( Rh = e/D ) and relative baffle pitch ( Rp = P/D ) in the range 0.046–0.115 and 0.46–1.15, respectively. For Reynolds number (5000 < Re < 17, 500), the numerical methodology is substantiated using experimental and theoretical correlations obtained from the literature. Smaller vortices near the sharp corners are removed by rounding the sharp edges, allowing the flow of fluid from inside and horizontal walls of the duct towards the semi-cylindrical sidewalls. This increases the overall turbulent kinetic energy. A peak augmentation of 3.24 and 4.03 times is obtained for Nusselt number ( Nu ) and friction factor ( f ), respectively, in contrast to conventional SAH. With a maximum enhancement of 127% in the effectiveness parameter relative to smooth SAH, this novel SAH design is evidently energy efficient. Based on CFD results, new correlations are developed in terms of Rh and Rp, which predicts the values with an absolute deviation of 4% and 7.4%, respectively. With lower exergy destruction, maximum enhancement in thermal and exergetic efficiency is obtained as 40.7% and 95.4%, respectively, for the proposed SAH relative to conventional SAH. Upon comparison with ribbed rectangular duct SAH configurations, the present design with semi-cylindrical side walls outperforms at all flow Re .